Using Lotus Notes as an intranet. - Falkner, Mike, 1954- (John Wiley & Sons, Inc., 1997)
"Learn how to leverage Lotus Notes' strengths as a groupware engine and tap the powerful Internet tools in Domino, the new generation of Notes servers. This practical guide to the use of Notes and the Internet to manage your business covers it all: from designing a system to take advantage of Notes and Domino-based tools to planning the installation and deploying the application. Using a balanced point of view that honestly discusses when and how to best use Notes, Domino, and Internet technologies, the book contains: • A complete analysis of typical business problems and how they can be solved with Notes, Domino, and the Internet • Cost analyses of implementing solutions to business problems • Step-by-step development of the systems needed to implement the solution using Notes and Domino, including home pages, order capture over the Internet, internal communication and workflow via Notes, and integration with a third-party accounting product for back-office processing and order fulfillment. Techniques for giving employees and managers insight into business information in the office or for externally using Notes and the internet." (Copied from the back cover).